The European Union’s climate policy towards Ukraine: normative power Europe in action? - Валерія Гуцалюк (Acta de Historia & Politica: Saeculum XXI)
The EU’s aspirations for leadership are also evident in regional and global climate policy, especially given the urgency of the problem of rising global temperatures. Since 2014, EU member states have been actively involved in shaping the organisation’s legislative framework on climate policy.